THE EFFECT OF TEACHER ERROR FEEDBACK ON THE ACCURACY OF EFL STUDENT WRITING - Yi-chun Pan (TEFLIN, 2010)
Abstract: This study investigated the effect of teacher error feedback on students ability to write accurately. Three male first-year Physics graduate students at a university in Taiwan participated in this study. They were asked to write a 100-word passage about the greatest invention in human history. Within days of the teacherâs grammatical feedback, the students were required to revise their work again based on the teachers suggested revisions. In addition, oral conferencing was conducted in order to help the students obtain a better comprehension of certain grammar points. Four weeks after the oral conferencing, the students were asked, without prior notice, to revise their original passages again. The findings reveal that the students made progress in the revised versions of their passages, but the success was not repeated in their later test versions. In other words, no positive relationship between teacher error feedback and studentsâ improvement in linguistic accuracy over time was observed. This suggests that teacher error feedback alone may not facilitate the learning of linguistic information. A combination of sufficient exposure to English in reading andÂ writing,Â plus opportunities to practice the language, for example, may lead to better grammar.